(3GdQSGdI GdTeSjI aj GdbhGYO GdefWbjIs - (3Ydj Hf YHO GdYRjR Hf MSGe Hf MGeO Hf Ce RGOg GdQhej,J (B980 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY fXe GdhLhO , hGNJQY eG gjGJ GdCTjGA HebJVi GdhLhO hHYO adeGcGf HEJaGb Cgd GdYbd hcGf GdEWdGY Ydi ObGFbgG dGjecf EdG HGdYde GdeQShe HGdefWb hSejJg hQJHJg Ydi ebOeI hebGdGJ hNGJeI s
(3BNQgG (B:s
(3JfbU ef BNQgG hBNQ GdehLhO efgG (B_ (3ai CKfGA GdebGdI GdKGdKI (B: (3hEdG aYcS GdUZQi hCeG GdTcd GdQGHY aTQW EfJGLg HMSH GdLgI CehQ NeSI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdYfGhjjf hGdahGJM HGdMeQI s
(3HBNQgG RLdjI ddTjN eMeO QTjO GdcjdGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs